Complement dysregulation in glomerulonephritis. (October 2019) - Kaartinen, Kati; Safa, Adrian; Kotha, Soumya; Ratti, Giorgio; Meri, Seppo
Abstract: Glomerulonephritis (GN) refers to a group of renal diseases affecting the glomeruli due to the damage mediated by immunological mechanisms. A large proportion of the disease manifestations are caused by disturbances in the complement system. They can be due to genetic errors, autoimmunity, microbes or abnormal immunoglobulins, like modified IgA or paraproteins. The common denominator in most of the problems is an overactive or misdirected alternative pathway complement activation. An assessment of kidney function, amount of proteinuria and hematuria are crucial elements to evaluate, when glomerulonephritis is suspected. However, the cornerstones of the diagnoses are renal biopsy and careful examination of the complement abnormality. Differential diagnostics between the various forms of GN is not possible based on clinical features, as they may vary greatly. This review describes the known mechanisms of complement dysfunction leading to different forms of primary GN (like IgA glomerulonephritis, dense deposit disease, C3 glomerulonephritis, post-infectious GN, membranous GN) and differences to atypical hemolytic uremic syndrome. It also covers the basic elements of etiology-directed therapy and prognosis of the most common forms of GN. Common principles in the management of GN include treatment of hypertension and reduction of proteinuria, some require immunomodulating treatment. Complement inhibition is an emerging treatment option. A thorough understanding of the basic disease mechanism and a careful follow-up are needed for optimal therapy.